Systemic Review of Cost-Effectiveness Studies of Trastuzumab Deruxtecan in the Treatment of Low-Her2-Expressive Advanced or Metastatic Breast Cancer - Thi Xuan, Bui; Thi Phuong Anh, Do; Thi Thu Thu, Tran; Ngoc Nghia, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Abstract: Trastuzumab Deruxtecan is an anti-HER2 monoclonal antibody drug conjugate linked to a topoisomerase I inhibitor via a cleavable linker based on a continuous 4-peptide chain. Objective: To synthesize and evaluate the quality of clinical efficacy studies of Trastuzumab Deruxtecan in the treatment of low- HER2-expressing advanced or metastatic breast cancer. Research methods: To conduct a systematic review of clinical efficacy studies of Trastuzumab Deruxtecan in the treatment of low- HER2-expressing advanced or metastatic breast cancer published up to the end of March 2025 in PubMed, Google Scholar, Cochrane Library and ScienceDirect databases. Research results: There were 08 studies included in the systematic review. All studies were of good quality when assessed using the CHEERS 2022 checklist with results meeting at least 22/26 criteria and at most 24/26 criteria. Out of the 08 studies, 03 showed that Trastuzumab Deruxtecan was cost-effective (37.5%), of which 01 study showed that this therapy was cost-effective in the HR-negative patient group, the remaining 05 studies did not meet cost-effectiveness (62.5%). The cost of Trastuzumab Deruxtecan was the most sensitive factor to the ICER results, with costs decreasing proportionally with the increase in the ability to achieve cost-effectiveness. Keywords: System overview, Trastuzumab Deruxtecan, low- HER2, metastatic breast cancer.